2000
DOI: 10.1152/ajpheart.2000.278.4.h1352
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression profile of an endothelial nitric oxide synthase promoter-reporter transgene

Abstract: Endothelium-derived nitric oxide (NO) is primarily attributable to constitutive expression of the endothelial nitric oxide synthase (eNOS) gene. Although a more comprehensive understanding of transcriptional regulation of eNOS is emerging with respect to in vitro regulatory pathways, their relevance in vivo warrants assessment. In this regard, promoter-reporter insertional transgenic murine lines were created containing 5,200 bp of the native murine eNOS promoter directing transcription of nuclear-localized be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 79 publications
4
56
0
1
Order By: Relevance
“…2 In contrast to the Leydig cell-restricted expression of the TnNOS promoter, we found that expression of the nuclear-localized Ϫ5200/ϩ28 Mu eNOSprom nls LacZ was active exclusively in the nuclei of vascular endothelium of mediumand large-sized arteries (Figure 4). Expression patterns were comparable in three independent 1, 5, and 10 copy number founders.…”
Section: Exclusive Expression Of the Ptnnos/placc/␣ 1 G Transgene In mentioning
confidence: 77%
See 1 more Smart Citation
“…2 In contrast to the Leydig cell-restricted expression of the TnNOS promoter, we found that expression of the nuclear-localized Ϫ5200/ϩ28 Mu eNOSprom nls LacZ was active exclusively in the nuclei of vascular endothelium of mediumand large-sized arteries (Figure 4). Expression patterns were comparable in three independent 1, 5, and 10 copy number founders.…”
Section: Exclusive Expression Of the Ptnnos/placc/␣ 1 G Transgene In mentioning
confidence: 77%
“…The nNOS (NOS1) isoform is expressed from a very complex human genomic locus spanning 240 kb at 12q24.2. 1 In contrast to the restricted endothelial cell-specific expression of the endothelial NOS (eNOS), 2 the nNOS isoform is constitutively expressed in a series of diverse cell types and tissues. 3 For instance, nNOS plays a fundamental role in the regulation of male sexual function.…”
mentioning
confidence: 99%
“…51,73,74 Constitutive expression is modulated by many factors, including laminar shear stress, cytokines, oxidized LDL, hypoxia, estrogen, and cell proliferation; and expression levels are regulated by transcription, mRNA stability, and epigenetics. [75][76][77][78] To determine whether shear stress-induced modulation of eNOS expression involves regulation of transcription, HAECs were exposed to uniform laminar shear stress, and the rate of transcription was determined by measuring hnRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…51 Expression of the nuclear-localized ␤-galactosidase reporter in these transgenic mice reflects eNOS promoter activity because previous studies demonstrated that expression of the reporter was highly comparable with endogenous eNOS, 51 which suggests that the transgenic promoter faithfully reflects transcriptional activity of endogenous eNOS. Histochemical staining revealed that nuclear localized expression of ␤-galactosidase was markedly diminished in the LC ( Figure 5, A and B).…”
Section: Transcription Of Enos Is Decreased In Arterial Regions Predimentioning
confidence: 97%
See 1 more Smart Citation